Synthesis and Spectral Characterization of Schiff Base Cr(III), Mn(III), and Fe(III) Novel Macrocyclic Complexes Derived from Thiocarbohydrazide and Dicarbonyl Compound. Issue 4 (2012) - Kumar, Gajendra; Devi, Shoma; Johari, Rajeev
Abstract : M(III) Schiff base macrocyclic complexes of the type [HLMX2] where M = Cr(III), Mn(III), Fe(III) and X = Cl, OAc have been synthesized by condensation of acetylacetone and Thio-carbohydrazide (2:2) in the presence of divalent metal salt in methanolic medium. The complexes have been characterized with the help of elemental analysis, conductance measurements, magnetic measurements and their structural configuration have been determined by various spectroscopic (electronic, IR, 1 H NMR, 13 C NMR, GCMS) techniques. Electronic and magnetic moments of the complexes indicate that the geometries of the metal centers are octahedral.